Study of Z boson plus jets events using variables sensitive to double-parton scattering in pp collisions at 13 TeV - (:unkn) unknown (SPRINGER, 2021)
Double-parton scattering is investigated using events with a Z boson and jets. The Z boson is reconstructed using only the dimuon channel. The measurements are performed with proton-proton collision data recorded by the CMS experiment at the LHC at root s = 13TeV, corresponding to an integrated luminosity of 35.9 fb(-1) collected in the year 2016. Differential cross sections of Z+ >= 1 jet and Z+ >= 2 jets are measured with transverse momentum of the jets above 20 GeV and pseudorapidity vertical bar eta vertical bar < 2.4. Several distributions with sensitivity to double-parton scattering effects are measured as functions of the angle and the transverse momentum imbalance between the Z boson and the jets. The measured distributions are compared with predictions from several event generators with different hadronization models and different parameter settings for multiparton interactions. The measured distributions show a dependence on the hadronization and multiparton interaction simulation parameters, and are important input for future improvements of the simulations.
Keywords: Hadron-Hadron scattering (experiments); Jets; PAIR PRODUCTION